Dependence of the capillary/vessel spatial pattern estimated by measuring diffuse reflectance spectra on the hemoglobin concentration level - Kanawade, Rajesh; Häußermann, Johannes; Klämpfl, Florian; Schmidt, Michael; Stelzle, Florian (Asia Communications and Photonics Conference, ACP, 2013)
The goal of this research is to study the behavior of the blood vessel density/spatial pattern estimated by measuring diffuce reflectance spectra depending on hemoglobin concentrations level for the application of early sign of the clinical shock detection. © OSA 2013.
CRIS-Team Scopus Importer:2023-03-07